KEADAAN MIKROBIOTA SALURAN CERNA PADA ANAK SEKOLAH DASAR YANG MENGALAMI STUNTING DI LOMBOK BARAT - Helmyati, Siti; Yuliati, Endri; Wisnusanti, Setyo Utami; Maghribi, Risnhukathulistiwi; Juffrie, Mohammad (Jurnal Gizi dan Pangan, 2017)
The purpose of this study was to compare the population of gut microbiota between the normal height and stunted in primary school children in West Lombok. The study design was observational study with comparative design. The study involved 115 primary school students with age 9-12 years old by simple random sampling. The research data included the measurement of height for age and gut microbiota analysis of faecal samples. Based on the results of t-test, the number of bacteria Lactobacillus in stunting group (6.96±0.94 log CFU/g) were significantly (p <0.05) lower than normal group (7,38±0,98 log CFU/g). The population of Bifidobacteria, Enterobacter, and E. coli were not different between the two group. However the trend of Bifidobacteria count in stunting group (8.19±0.74 log CFU/g) was lower than normal group (8.22±0.79 log CFU/g) while the number of Enterobacter and E. coli in stunting group (7.82±0.68 and 7.03±0.97 log CFU/g) were higher than the normal group (7.71±0.81 and 6.96±1.22 log CFU/g).